2001
DOI: 10.1002/app.1951
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cooling rate on pVT‐data of semicrystalline polymers

Abstract: For numerical simulations of the injection moulding process, an accurate description of the specific volume is needed to predict differential shrinkage during and after moulding, which causes thermally induced stresses and controls the dimensional accuracy and long term dimensional stability. For amorphous polymers, for which often it can be assumed that cooling rate dependence can be ignored, standard techniques enable measurements of the specific volume as a function of temperature and pressure. For semi-cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…Finally it should be noted that an analysis based on rate equations, such as [3,8] and the present one, may provide a basis for a variety of generalizations, see [17,[43][44][45][46][47][48][49][50][51] for examples.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Finally it should be noted that an analysis based on rate equations, such as [3,8] and the present one, may provide a basis for a variety of generalizations, see [17,[43][44][45][46][47][48][49][50][51] for examples.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, for calculating the temperature additional information of the material, e.g. pvT-relations, must be known in detail, since process parameters like cooling rate influence this behaviour [19]. In addition, the models, especially the designed system matrix and thus the propagation behaviour of the ultrasound wave, underlay no disturbing effects in the virtual test problems.…”
Section: Virtual Test Problemsmentioning
confidence: 99%
“…Particularly, pvT data for semi-crystalline materials have been shown by Zuidema et al and Gao et al [3,4] to be dependent on the cooling rate at which they have been characterized. They showed that at very low cooling rate (0.017°C/s) it matched data from the available database, but at higher cooling rate (40°C/s), the crystallization transition is shifted to lower temperature.…”
Section: Introductionmentioning
confidence: 99%